What are centered worlds? - Liao, Shen-yi. (2014)
David Lewis argues that centered worlds give us a way to capture de se, or self-locating, contents in philosophy of language and philosophy of mind. In recent years, centered worlds have also gained other uses in areas ranging widely from metaphysics to ethics. In this paper, I raise a problem for centered worlds and discuss the costs and benefits of different solutions. My investigation into the nature of centered worlds brings out potentially problematic implicit commitments of the theories that employ them. In addition, my investigation shows that the conception of centered worlds widely attributed to David Lewis is not only problematic, but in fact not his.